PERANCANGAN SISTEM BRINE COOLING PADA SHOWCASE DAN KABIN HIDROPONIK UNTUK TANAMAN KANGKUNG (IPOMOEA AQUATICA) - Lukitobudi, Arda Rahardja; Prasetyo, Bowo Yuli; Harish, M. Fasya Nur; Fadhil, Dimas Alif (KURVATEK, 2021)
Limited area and pollution in the city and also weather problem can become an obstacle to planting kale (Ipomoea Aquatica). Post harvest storage of kale also usually does not conditioned which quickly wilted and not fresh. To create an optimum environment, it was necessary to control environment factors such as air temperature, humidity, light intensity, growing media temperature and humidity, and the availability of nutrients [2]. Tofu and wood waste as a hydroponic nutrients [1] not all area were available so in this research AB Mix nutrient was used. In this research, refrigerated showcase by brine cooling was used [3][4]. Hydroponic planting system method used in this research was Deep Flow Technique which the kale (Ipomoea Aquatica) was planted in a water layer 4-6 cm deep in conditioned showcase of 20-30 0C and 60% humidity. Brine cooling was used to condition the showcase from seed to post harvest and was observed its growth. Post harvest conditioned storage was also complete the showcase more durable. By brine cooling system to cool brine in the range of 70C to 170, the product storage cabin was maintained at 8,70C to 10,50C and the showcase cabin was maintained at 20,40C to 23,60C. The brine cooling system has COPactual of 3,98 and COPcarnot of 6,65 with system efficiency of 59,8%. Keywords: Hydroponic, Ipomoea Aquatica, showcase, brine cooling, Deep Flow Technique.